2016
DOI: 10.1371/journal.pntd.0004821
|View full text |Cite
|
Sign up to set email alerts
|

Safety Overview of a Recombinant Live-Attenuated Tetravalent Dengue Vaccine: Pooled Analysis of Data from 18 Clinical Trials

Abstract: A recombinant live attenuated tetravalent dengue vaccine (CYD-TDV) has been shown to be efficacious in preventing virologically-confirmed dengue disease, severe dengue disease and dengue hospitalization in children aged 2–16 years in Asia and Latin America. We analyzed pooled safety data from 18 phase I, II and III clinical trials in which the dengue vaccine was administered to participants aged 2–60 years, including long-term safety follow-up in three efficacy trials. The participants were analyzed according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…2 Although this potential risk was observed, the vaccine demonstrated a good safety and efficacy profile in pooled analyses of clinical trials in the indicated age group of ≥9 years. [3][4][5] The safety and immunogenicity of CYD-TDV was previously investigated in two phase II studies in Vietnam and Singapore, countries with high and low dengue endemicity, respectively. 6,7 We present here the four-year follow-up of these participants (aged <9 and ≥9 years) after the third vaccine dose in two study populations to assess the persistence of immunogenicity and safety of CYD-TDV.…”
Section: Introductionmentioning
confidence: 99%
“…2 Although this potential risk was observed, the vaccine demonstrated a good safety and efficacy profile in pooled analyses of clinical trials in the indicated age group of ≥9 years. [3][4][5] The safety and immunogenicity of CYD-TDV was previously investigated in two phase II studies in Vietnam and Singapore, countries with high and low dengue endemicity, respectively. 6,7 We present here the four-year follow-up of these participants (aged <9 and ≥9 years) after the third vaccine dose in two study populations to assess the persistence of immunogenicity and safety of CYD-TDV.…”
Section: Introductionmentioning
confidence: 99%
“…The consistent pattern of transient, early-onset (<24 h) local arm pain and tenderness accompanied by systemic symptoms is commensurate with that of other live attenuated viral vaccines. [18][19][20] When examined by dose group or grouped dichotomously, a dose-related increase was observed in the incidence and, in some cases, severity of solicited local and systemic adverse events. The early acute phase reactogenicity was associated with low-level viraemia, which peaked on days 1-2.…”
Section: Discussionmentioning
confidence: 99%
“…Unpublished exploratory analyses of vaccinated cases from the Dengvaxia Phase 2b trials suggest a relationship between nAb titers and probability of disease [45]. Further, the Phase 3 clinical trials showed an overall positive efficacy (protection against having a dengue case) of the vaccine during the initial 25 months of the trial, but evidence of reduced protective immunity over the follow-up period, with more hospitalized dengue cases in vaccinees than placebos >1 year after the final vaccine dose in children <9 years old [46,47]. …”
Section: Immune Responses In the Context Of Dengue Vaccinesmentioning
confidence: 99%